Analisis Strategi Pemasaran Pada Penginapan Syariah Ikhlas Beramal Bangkalan Ditinjau Dari Etika Bisnis Islam - Tivani, Tivani Adelia Putri; Dahruji (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
Marketing strategy is a design of goals and objectives in the field of marketing, which contains directions related to activities that will be carried out in order to realize a company's marketing objectives. In the marketing mix, there are the most appropriate marketing tools which are usually referred to as the 7Ps, these terms include (product, price, place, promotion, people, physical evidence, process). The next theory used in this research is the theory of Islamic business ethics, which is an activity or series of business activities that refers to Islamic principles and has the aim of remembering Allah SWT in the context of worship. The principles underlying Islamic business ethics include (unity, equilibrium, responsibility, benevolence, free will). The purpose of this research is to analyze and describe how the marketing strategies implemented by accommodation are viewed from Islamic business ethics. The research method used is qualitative research with the type of field research. The results of this research are qualitative research with a descriptive approach, where data is collected through documentation, interviews and observations and then analyzed using inductive data analysis techniques. This research produces a marketing strategy concept that is in accordance with the 7P concept, which has been adapted to sharia provisions. This research can also be a basis for sharia lodging businesses in accordance with Islamic sharia.